Translation and cultural adaptation with specific reference to Tshivenda and English - Mashamba, Mabula (University of Limpopo, 2011)
The aim of this study was to investigate the problems encountered by translators when translating medical terms from English into Tshivenda. It has been revealed in this study that the major problem that the translators are confronted with is lack of terminology in the specialized field such as Health. This problem is caused by the fact that different languages entail a variety of culture. The study revealed that most translators and lexicographers resort to transliteration and borrowing when confronted with zero-equivalence. They regard transliteration and borrowing as the quickest possible strategies. The study discovered that transliteration should not be opted as an alternative strategy to deal with zero-equivalence as users will be led to a state of confusion. The study revealed that communicative translation is regarded as the most fruitful method of translation as it conveys the exact message of the original in a best possible manner. Both the source and the target users get the same message.
Thesis (M.A.(African language))--University of Limpopo, 2011
Keywords: Translation; Culture; Source langauge; Target language; Venda language; Translating and interpreting